Teledentistry in Jordan: assessing knowledge and attitudes among dentists - Tamadur Mahmoud Falah; Sabha Mahmoud Alshatrat; Jumana M. Sabarini; Majd M. Alsaleh; Yousef Saleh Khader; Alaa Fawwaz Dalky; Bayan Jamal Almahasneh; Abedelmalek Kalefh Tabnjh; Abedelmalek Kalefh Tabnjh; Abedelmalek Kalefh Tabnjh (Frontiers in Oral Health)
Aimto evaluate the perceptions, knowledge, and attitudes of Jordanian dentists towards teledentistry.MethodsA web-based, anonymous, self-administered closed-end questionnaire was distributed across Jordan. Conducted with a sample of 250 dentists selected through convenience sampling, the research assessed knowledge and attitudes using a pre-designed and validated questionnaire. An electronic link was sent to active Jordanian Dental Association (JDA) members. The survey consisted of three sections with closed questions.ResultsA total of 250 dentists (Male 52%) participated in the study. The mean knowledge and attitude scores were 78.78 ± 15.27 and 76.81 ± 14.74, respectively. Dentists without postgraduate qualifications demonstrated significantly greater knowledge compared to those with postgraduate qualifications (p = 0.023). Over half of the respondents agreed that teledentistry is effective for diagnosing and providing treatment recommendations from a distance and can assist in monitoring patients' oral health. However, the majority disagreed with its application across all branches of dentistry. A significant number of participants believed that teledentistry could improve access to oral healthcare, reduce costs, save time for dentists, increase accessibility in rural and underserved areas, and reduce isolation among practitioners by facilitating peer contact and specialist support. T-test and one-way ANOVA were used to test the mean difference of the knowledge and attitude percentages for the subcategories. Chi-square tests revealed a significant association between knowledge and attitude toward teledentistry and demographic characteristics of the participants. Also, the test revealed a significant difference in respondents' workplace settings regarding their views on teledentistry's impact on monitoring patients' oral health (p = 0.026), its potential for integration into current dental services (p = 0.001), and time-saving benefits (p = 0.007). The results suggest participants with less than 10 years of experience were more likely to agree that teledentistry can improve access to oral health care (p = 0.039). Similarly, participants also more likely to agree that teledentistry has the potential to be integrated into current dental services (p = 0.029).ConclusionTeledentistry has the potential to provide equitable, cost-effective, and high-quality dental care especially for individuals in remote areas with limited access to traditional dental care.